2020
DOI: 10.12659/msm.923619
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Double-Arm Digital Subtraction Angiography (DSA)-Guided and C-Arm-Guided Percutaneous Kyphoplasty (PKP) to Treat Senile Osteoporotic Vertebral Compression Fractures

Abstract: Background Osteoporotic vertebral compression fracture (OVCF) is a common fracture in the elderly. Conservative treatment requires prolonged bedding, which may lead to serious complications. To explore optimized use of percutaneous kyphoplasty (PKP) in the treatment of senile osteoporotic thoracolumbar vertebral compression fractures, in this study, we used C-arm-guided and double-arm digital subtraction angiography (DSA)-guided PKP to treat OVCF in elderly patients and analyzed the effective reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 17 When designing the puncture path before the operation, the puncture angle can be appropriately increased, and the puncture needle can be guided to penetrate the vertebral body one time by DSA three-dimensional scanning during operation so that the end of the working channel is as close as possible to the middle line of the vertebral body. 18 The results demonstrated that the puncture angle of the DSA-guided group was significantly larger than that of the traditional fluoroscopy group, which may be one of the reasons for the more uniform distribution of bone cement in DSA guided group. Related studies have demonstrated that DSA-guided surgery can reduce intraoperative fluoroscopy times and radiation injury.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“… 17 When designing the puncture path before the operation, the puncture angle can be appropriately increased, and the puncture needle can be guided to penetrate the vertebral body one time by DSA three-dimensional scanning during operation so that the end of the working channel is as close as possible to the middle line of the vertebral body. 18 The results demonstrated that the puncture angle of the DSA-guided group was significantly larger than that of the traditional fluoroscopy group, which may be one of the reasons for the more uniform distribution of bone cement in DSA guided group. Related studies have demonstrated that DSA-guided surgery can reduce intraoperative fluoroscopy times and radiation injury.…”
Section: Discussionmentioning
confidence: 80%
“…Related studies have demonstrated that DSA-guided surgery can reduce intraoperative fluoroscopy times and radiation injury. 12 , 18 Furthermore, a recent study demonstrated that PKP guided by DSA could reduce the times and doses of fluoroscopy. 19 However, there is no report on the fluoroscopy dose of PKP guided by DSA in treating multi-vertebral osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%